Estratégia de rastreamento de máxima potência (MPPT) sem uso de sensores mecânicos para aerogeradores de pequeno porte - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The lack of natural resources and global warming has called for the use of renewable energy sources, a scenario that has encouraged the generation of wind energy on a national and global scale. Regarding small-scale generation, many of the systems do not have mechanisms to keep small wind turbines at their optimum, due the stochastic nature of the wind they are subjected to. In this context, two maximum power point tracking (MPPT) strategies are presented for low power wind turbines. The physical characteristics of the wind energy conversion are discussed, as well as the development of a model for the simulation of the conversion system, which includes a wind turbine emulator coupled to the generator, a Boost CC-CC converter for energy processing and a generator circuit of time series of wind speed. First, a perturbation and Observation algorithm (P&O) with _xed increment is presented. Afterwards, a MPPT algorithm based on Fuzzy logic was developed in the simulation environment of the MATLAB Simulink® and PSIM® software, and it is also implemented in C language. Lastly, simulation results are presented to show the advantages and disadvantages of each MPPT strategy.
Keywords: Engenharia elétrica; Conversores elétricos; Fontes renováveis de energia; Lógica Fuzzy; Aerogeradores; Electrical engineering; Electrical converters; Renewable sources of energy; Fuzzy logic; Wind Turbines; CNPQ::ENGENHARIAS